Animal bone (Scottish Historical and Archaeological Internet Reports, 2003)
The animal bones from these three Borders sites have shown that assumptions based on material from urban excavations in the north-east of Scotland do not necessarily hold true for every other Scottish site. This is particularly so for the evidence from medieval and post-medieval phases at Bridgegate, Peebles, where sheep bones dominated over those of cattle. Thus far, discussions of the pattern of animal exploitation in the medieval and post-medieval periods have relied on results from north-easterly sites, mainly towns, and have concluded that the economy relied more heavily on cattle that on sheep. The bones from Peebles proved the evidence to show that sheep, the producers of wool and thence textiles, play a far more important role that cattle in the Borders region.